2004
DOI: 10.1161/01.atv.0000144009.35400.65
|View full text |Cite
|
Sign up to set email alerts
|

Altered PDGF-BB–Induced p38 MAP Kinase Activation in Diabetic Vascular Smooth Muscle Cells

Abstract: Objective-We investigated the regulation of p38 mitogen-activated protein kinase (MAPK) by platelet-derived growth factor (PDGF)-BB and its biological effects in cultured normal and diabetic rat vascular smooth muscle cells (VSMCs). Methods and Results-VSMC growth from diabetic rats was faster than that from normal rats. The expression of the PDGF ␤-receptor in diabetic VSMCs was significantly elevated compared with that in normal cells, and PDGF-BB-induced p38 phosphorylation in diabetic cells was more enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
6
34
1
Order By: Relevance
“…Thus, these results suggest that PKCd regulates antigen presentation by molecules that acquire their antigens in the endocytic pathway, but not by those that present endogenous peptide ligands to CTL. It has been reported that PKCd plays a role in the control of MAPK-mediated signaling, mainly upstream of p38 and ERK1/2 [7][8][9], and we have recently demonstrated that both p38 and ERK1/2 participate in the regulation of CD1d-mediated antigen presentation [2]. Interestingly, the phosphorylation of both p38 and ERK1/2 was decreased in the DN PKCd-expressing cells as compared to the control (Fig.…”
Section: Expression Of a Dominant-negative Pkcd Impairs Cd1d-mediatedmentioning
confidence: 59%
“…Thus, these results suggest that PKCd regulates antigen presentation by molecules that acquire their antigens in the endocytic pathway, but not by those that present endogenous peptide ligands to CTL. It has been reported that PKCd plays a role in the control of MAPK-mediated signaling, mainly upstream of p38 and ERK1/2 [7][8][9], and we have recently demonstrated that both p38 and ERK1/2 participate in the regulation of CD1d-mediated antigen presentation [2]. Interestingly, the phosphorylation of both p38 and ERK1/2 was decreased in the DN PKCd-expressing cells as compared to the control (Fig.…”
Section: Expression Of a Dominant-negative Pkcd Impairs Cd1d-mediatedmentioning
confidence: 59%
“…It has been reported that PDGF stimulates SMC migration and proliferation through activation of multiple kinases, such as the PI3K/Akt, 40 MEK-ERK, 41 JNK, 42 and p38 43 pathways. The above data indicate that activation of XBP1 splicing is sufficient to induce SMC migration and proliferation, although it is not necessary for PDGF-induced migration.…”
Section: Xbp1s Increased Smc Migration Via the Pi3k/akt Pathwaymentioning
confidence: 99%
“…In addition, consistent with our present findings, it has been reported that PDGF-induced p38 ffMAP kinase activation regulated cell migration in VSMCs K ISHIZAWA, N DORJSUREN and others . Adiponectin inhibits PDGF-induced RMC migration (Zhan et al 2003, Yamaguchi et al 2004. We have already demonstrated that adiponectin inhibited IGF-1-induced cell migration through suppression of ERK1/2 activation, which might be implicated in AMPK activation in VSMCs (Motobayashi et al 2009).…”
Section: Discussionmentioning
confidence: 95%